PEMANFAATAN GLISEROL DAN PATI SAGU SEBAGAI EDIBLE COATING PADA PENYIMPANAN JERUK SIAM MADU (Citrus nobilis) - Healthy Aldriany Prasetyo; Ferimawati Laia (Universitas Quality, 2018)
This study aims to determine the effect of adding glycerol and sago starch as edible coating on the quality of honey citrus fruits during storage and to determine the quality and freshness quality of siamese citrus honey after the addition of glycerol and sago starch as edible coatings on the quality of honey siam during storage . This study used a non-factorial Completely Randomized Design (RAL) arranged in factorial with 2 factors. Factor I: Comparison of glycerol, sago starch and distilled water. G0 = 0 ml glycerol concentration (control) + sago starch 10 gram + 500 ml distilled water, G1 = glycerol concentration 2ml + sago starch 10 gram + 500 ml distilled water, G2 = 4 ml glycerol concentration + sago starch 10 gram + aquades 500 ml, G3 = 6 ml glycerol + sago starch concentration 10 gram + 500 ml distilled water, G4 = 8 ml glycerol concentration + 10 sago starch + 500 ml distilled water. Factor II: Duration of storage (days). H0 = 0 days, H1 = 3 days, H2 = 6 days, H3 = 9 days, H4 = 12 days, H5 = 15 days. The results showed that the concentration of glycerol and starch of sago as edible coating on the quality of citrus honey during storage was significantly different from the weight loss with the concentration of glycerol = 8 ml at storage (15 days) which was 0.27%; and followed by Vitamin C significantly different from storage (12 days) with glycerol concentration = 0.06%, then total different acids were not significant at storage (15 days) with 0.02% glycerol concentration and different colors not significant with 1 ml glycerol concentration on storage (6 days) which is = 4.00%.